Navigating infection risk during oviposition and cannibalistic foraging in a holometabolous insect. (9th August 2018) - Siva-Jothy, Jonathon A; Monteith, Katy M; Vale, Pedro F
Abstract : To stay healthy, animals should avoid sources of infection. However, some important behaviors, such as foraging and reproduction, can increase infection risk. We tested experimentally whether fruit flies avoided infected food sources when foraging as larva and deciding where to lay eggs as adults. Larvae did not avoid infected food when foraging. Mothers however, sometimes avoided laying eggs on infectious food. Abstract: Deciding where to eat and raise offspring carries important fitness consequences for all animals, especially if foraging, feeding, and reproduction increase pathogen exposure. In insects with complete metamorphosis, foraging mainly occurs during the larval stage, while oviposition decisions are made by adult females. Selection for infection avoidance behaviors may therefore be developmentally uncoupled. Using a combination of experimental infections and behavioral choice assays, we tested if Drosophila melanogaster fruit flies avoid infectious environments at distinct developmental stages. When given conspecific fly carcasses as a food source, larvae did not discriminate between carcasses that were clean or infected with the pathogenic Drosophila C Virus (DCV), even though cannibalism was a viable route of DCV transmission. When laying eggs, DCV-infected females did not discriminate between infectious and noninfectious carcasses, and laying eggs near potentially infectious carcasses was always preferred to sites containing only fly food. Healthy mothers, however, laid more eggs near a clean rather than an infectious carcass. Avoidance during oviposition changed over time: after an initial oviposition period, healthy mothers stopped avoiding infectious carcasses. We interpret this result as a possible trade-off between managing infection risk and maximizing reproduction. Our findings suggest infection avoidance contributes to how mothers provision their offspring and underline the need to consider infection avoidance behaviors at multiple life-stages.